If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11.2 + -2x = x Solving 11.2 + -2x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 11.2 + -2x + -1x = x + -1x Combine like terms: -2x + -1x = -3x 11.2 + -3x = x + -1x Combine like terms: x + -1x = 0 11.2 + -3x = 0 Add '-11.2' to each side of the equation. 11.2 + -11.2 + -3x = 0 + -11.2 Combine like terms: 11.2 + -11.2 = 0.0 0.0 + -3x = 0 + -11.2 -3x = 0 + -11.2 Combine like terms: 0 + -11.2 = -11.2 -3x = -11.2 Divide each side by '-3'. x = 3.733333333 Simplifying x = 3.733333333
| -(6y+4)-(-5y-6)=1 | | 3(2p+2)=5(-3p-3) | | 9x-15=3x+6 | | 9x+4=66 | | -0.3d+(-2.8)=-4 | | 8(1+-2*.02)= | | (4x^2y^3)(5xy^3)=0 | | 24*.02= | | 10x^2+89x-9=0 | | 20-4u+3=5u-8+2u | | 0.06t-2.9=7 | | 4g+9=5g | | 9(a+1)-2(a-2)= | | 162050+x=320750 | | q^2=4q+77 | | 0.09d-0.14=0.67 | | 162050*x=320750 | | -7+4n=2n+-15 | | 4+6c+13=7c-5-c | | 9s+12=9s+27 | | 6x-18x^2=0 | | y=6x-18x^2 | | 4+68+13=7c-5-c | | 4b+12=35 | | 3a+2.1+4a=-0.7 | | G+(-5)=4 | | c*3= | | a+8=75 | | 5x^2=6-12x | | 3c=21 | | 4a-7+(7-3a)= | | 5-(-66)= |